C iv emission-line properties and systematic trends in quasar black hole mass estimates. Issue 1 (9th June 2016) - Coatman, Liam; Hewett, Paul C.; Banerji, Manda; Richards, Gordon T.
Abstract: Black hole masses are crucial to understanding the physics of the connection between quasars and their host galaxies and measuring cosmic black hole-growth. At high redshift, z ≳ 2.1, black hole masses are normally derived using the velocity width of the C iv $\tt λ λ$ 1548, 1550 broad emission line, based on the assumption that the observed velocity widths arise from virial-induced motions. In many quasars, the C iv emission line exhibits significant blue asymmetries ('blueshifts') with the line centroid displaced by up to thousands of km s −1 to the blue. These blueshifts almost certainly signal the presence of strong outflows, most likely originating in a disc wind. We have obtained near-infrared spectra, including the Hα $\tt λ$ 6565 emission line, for 19 luminous ( L Bol = 46.5–47.5 erg s −1 ) Sloan Digital Sky Survey quasars, at redshifts 2 < z < 2.7, with C iv emission lines spanning the full range of blueshifts present in the population. A strong correlation between C iv velocity width and blueshift is found and, at large blueshifts, >2000 km s −1, the velocity widths appear to be dominated by non-virial motions. Black hole masses, based on the full width at half-maximum of the C iv emission line, can be overestimated by a factor of 5 at large blueshifts. A larger sample of quasar spectra with both C iv and H β, or Hα, emission lines will allow quantitative corrections to C iv -based black hole masses as a function of blueshift to be derived. We find that quasars with large C iv blueshifts possess high Eddington luminosity ratios and that the fraction of high-blueshift quasars in a flux-limited sample is enhanced by a factor of approximately 4 relative to a sample limited by black hole mass.